THE STUDY OF WOMEN'S HEALTH ACROSS THE NATION (SWAN): FROM MIDLIFE ONWARD. (8th November 2019) - Avis, Nancy E; Avis, Nancy E; Crawford, Sybil; Colvin, Alicia; Derby, Carol A; Karvonen-Gutierrez, Carrie; Brooks, Maria M
Abstract: The Study of Women's Health Across the Nation (SWAN) is a multisite, multiracial/ethnic longitudinal study of women initially aged 42-52 (N=3302) designed to characterize the physiological and psychosocial changes that occur during the menopause transition and to assess their relations to subsequent health and age-related diseases. Each of seven clinical sites recruited non-Hispanic white women and women belonging to a predetermined racial/ethnic minority (African American, Hispanic, Chinese, or Japanese). Cohort eligibility was determined from a cross-sectional survey of 16, 065 women in 1996-97 aged 40-55 who were aged 42-52, had an intact uterus and at least one ovary, and not using hormone therapy. Cohort participants have been assessed in-person approximately annually through follow-up visit 15 in 2017 using a standardized protocol of detailed questions about medical, reproductive and menstrual history; lifestyle and psychosocial factors; physical and psychological symptoms; and anthropometric measurements, reproductive hormones, bone and body composition, and cardiovascular health.